Instructors' perception on integrating a learning management system in teaching ESL adult learners online reading / Nor Fazlin Mohd, Saadiyah Darus, Nadzrah Abu Bakar - Mohd, Nor Fazlin; Darus, Saadiyah; Abu Bakar, Nadzrah (UPENA, 2015)
Most educational institutions utilize Learning Management Systems (LMSs)as learning and teaching portal for online learning programmes. It isa system that allows the institution to manage and monitor instructors, learners and content of courses. Nonetheless, due to this relatively new learning environment, most online teaching methods have not yet incorporated pedagogic principles in which could lead to ineffective teaching thus resulting in unsuccessful learning. In Second Language teaching and learning, it is crucial for instructors to understand and utilize this system for online language learning. Although, the LMS may provide the tools and features that could support teaching in an online learning environment, the lack of instructors' understanding of an LMS environment may prevent learning from taking place.